Three-dimensional modeling of granular flow impact on rigid and deformable structures. (August 2019) - Zhan, Ling; Peng, Chong; Zhang, Bingyin; Wu, Wei
Abstract: A stabilized coupled total-Lagrangian and conventional Euler kernel based smoothed particle hydrodynamics (TL-CE SPH) method is presented to model three-dimensional granular flow-structure interaction with rigid and deformable structures. In the coupled TL-CE SPH, the granular material is simulated using CESPH with the Dracker-Prager model, while the structure solver is based on TLSPH. The stabilized TLSPH with corrected kernel gradient, Lagrangian kernel function and hourglass control technique overcomes the common deficiencies of inconsistency, tensile instability and hourglass mode in structure modeling. Based on the Adami boundary condition (Adami et al., 2012), a unified framework for modeling solid boundaries and the granular media-structure interfaces is presented. Furthermore, the advanced GPU-acceleration is employed to achieve high efficiency. The coupled method is employed to simulate problems of granular collapse, granular material-structure interaction at quasi-static regime and granular flows impact on rigid and deformable structures. The presented method can simulate granular flows, the flow-structure interactions, and the deformation and stress of the structures correctly. Furthermore, the GPU-acceleration gives hundreds times of speed-up over serial CPU implementation. The presented method can be applied to large scale three-dimensional cases.